THE EUSTACHIAN TUBE FUNCTION TEST IN HEALTHY SUBJECTS - Tsuji, Tomihiko; Sekine, Taiki (JIBI INKOKA TEMBO, 2019)
The eustachian tube function was investigated in 100 ears of 50 healthy individuals in their 20s to 50s with no ear disease, by inspecting the opening of the eustachian tube (ET) using sonotubometry and impedance methods (Valsalva maneuver, Toynbee maneuver, deep breathing, and sniffling). Of the 100 ears, the ET opening was found to be positive patent by sonotubometry in 82.0%, with during the Valsalva maneuver in 82.0%, and with during the Toynbee maneuver in 65.0%, and by all three methods in 51%. In sonotubometry, the duration of tubal opening ranged from 105 to 2,455 msec, with a mean of 569.5 msec. The ET opening was negative closed in a total of 35 ears by sonotubometry or during the Valsalva maneuver, and it was considered that these ears were at a higher risk of middle ear pressure injury. A total of 16 ears showed a “prolonged duration” of opening of more than 1,000 msec, or “movement of the tympanic membrane” during deep breathing or sniffling, and were believed to be at a higher risk of showing a patulous Eustachian tube in the presence of some trigger. It may be necessary to evaluate the ET status comprehensively based on a subject's symptoms, physical findings, and results of multiple ET function tests.